Global Status of Phytoplasma Diseases in Vegetable Crops - Kumari, Shweta; Nagendran, Krishnan; Rai, Awadhesh Bahadur; Singh, Bijendra; Rao, Govind Pratap; Bertaccini, Assunta (Frontiers in Microbiology, 2019)
The presence of phytoplasmas and their associated diseases is an emerging threat to vegetable production which leads to severe yield losses worldwide. Phytoplasmas are phloem-limited pleomorphic bacteria lacking the cell wall, mainly transmitted through leafhoppers but also by plant propagation materials and seeds. Phytoplasma diseases of vegetable crops are characterized by symptoms such as little leaf, phyllody, flower virescence, big bud and witches' brooms. Phytoplasmas enclosed in at least sixteen different ribosomal groups infecting vegetable crops have been reported thus far across the world. The aster yellows phytoplasma group (16SrI) is presently prevalent, followed by the peanut witches’ broom (16SrII). Wide and overlapping crop and non-crop host ranges of phytoplasmas, polyphagous insect vectors, limited availability of resistance sources and unavailability of environmentally safe chemical control measures lead to an arduous effort in the management of these diseases. The most feasible control of vegetable phytoplasma diseases is a consequence of the development and implementation of integrated disease management programmes. The availability of molecular tools for phytoplasma identification at the strain level greatly facilitated this kind of approach. It is moreover essential to understand the molecular basis of phytoplasma-vector interaction, epidemiology and other factors involved in disease development in order to reduce the disease outbreaks. Information on the knowledge about the most widespread phytoplasma diseases in vegetable crops is reviewed here in a comprehensive manner.